Insects found in birds’ nests from Argentina. Pseudoseisura lophotes Reichenbach, 1853 and Anumbius annumbi (Vieillot, 1817) (Aves: Furnariidae), hosts of Triatoma platensis Neiva, 1913 (Hemiptera: Reduviidae: Triatominae) - Paola, Turienzo (Zootaxa, 2014)
The insect fauna of the nests of Pseudoseisura lophotes (Reichenbach, 1853) (Aves: Furnariidae) from Argentina was investigated. A total of 110 species (68 identified to species, 22 identified to genus, 20 identified to family) in 40 families of 10 orders of insects was found in these nests. Triatoma platensis Neiva, 1913 (Hemiptera: Reduviidae) was found again in nests of P. lophotes, corroborating after 73 years the first observations made by Mazza in 1936. The occurrence of the insects in nests of P. lophotes is compared with the previously known insect fauna in nests of A. annumbi, Furnarius rufus (Furnariidae), and Myiopsitta monachus (Psittacidae). The insect fauna in additional nests of Anumbius annumbi from the same and/or different localities is given, and used in comparisons. The first occurrence of Cuterebridae (Diptera) in birds’ nests, their pupae as the overwintering stage, and the second simultaneous infestation by two species of Philornis (Diptera: Muscidae) on the same nestlings are presented. Other simultaneous infestations of different hematophagous arthropods (Hemiptera: Cimidae; Reduviidae: Triatominae, and Acari: Argasidae) are remarked and discussed.